2021
DOI: 10.3390/pharmaceutics13081134
|View full text |Cite
|
Sign up to set email alerts
|

The Cysteine-Containing Cell-Penetrating Peptide AP Enables Efficient Macromolecule Delivery to T Cells and Controls Autoimmune Encephalomyelitis

Abstract: T cells are key immune cells involved in the pathogenesis of several diseases, rendering them important therapeutic targets. Although drug delivery to T cells is the subject of continuous research, it remains challenging to deliver drugs to primary T cells. Here, we used a peptide-based drug delivery system, AP, which was previously developed as a transdermal delivery peptide, to modulate T cell function. We first identified that AP-conjugated enhanced green fluorescent protein (EGFP) was efficiently delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…They are crucial immune cells involved in the pathogenesis of many diseases, rendering them an essential therapeutic target. Kim et al 86 utilized a unique transdermal delivery peptide called AP, consisting of nine amino acids, which was derived from the human astrotactin-1 protein. The purpose of this peptide was to specifically target T cells with a T cell modulatory protein, namely ctCTLA-4.…”
Section: ■ Cpps For Cns Diseases Treatmentmentioning
confidence: 99%
“…They are crucial immune cells involved in the pathogenesis of many diseases, rendering them an essential therapeutic target. Kim et al 86 utilized a unique transdermal delivery peptide called AP, consisting of nine amino acids, which was derived from the human astrotactin-1 protein. The purpose of this peptide was to specifically target T cells with a T cell modulatory protein, namely ctCTLA-4.…”
Section: ■ Cpps For Cns Diseases Treatmentmentioning
confidence: 99%
“…A study reported that CTLA-4 signaling peptide can induce Treg cells and inhibit the activity of MS ( 131 ) ( Figure 3C ). Furthermore, a cysteine-containing cell-penetrating peptide (AP)-conjugated CTLA-4 cytoplasmic domain (AP-ctCTLA-4) peptide attenuated the activity of EAE by inhibiting IL-17A expression and reducing the number of pathogenic IL-17A + GM-CSF + CD4 T cells ( 132 ). The results suggest that CTLA-4 is a target for the treatment of MS.…”
Section: Ctla-4: In the Development Of Autoimmune Diseasesmentioning
confidence: 99%
“…Moreover, Kim et al have identified another interesting approach [ 110 ]. They synthesized an AP-ctCTLA-4 peptide to modulate the T cell function in a mouse model of EAE, and they showed that AP-ctCTLA-4 decreased IL-17A expression under Th17 differentiation conditions in vitro and improved EAE, with reduced numbers of pathogenic IL-17A + GM-CSF + CD4 T cells.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…They synthesized an AP-ctCTLA-4 peptide to modulate the T cell function in a mouse model of EAE, and they showed that AP-ctCTLA-4 decreased IL-17A expression under Th17 differentiation conditions in vitro and improved EAE, with reduced numbers of pathogenic IL-17A + GM-CSF + CD4 T cells. Both male and female animals were used for the experimental procedures [ 110 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%